Leukemia detection from blood smears - Faivdullah, Lokman; Azahar, Farid; Htike@Muhammad Yusof, Zaw Zaw; Nyein Naing, Wai Yan (Engineering and Technology Publishing, 2015)
Leukemia is a highly fatal hematologic cancer which starts in blood-forming tissue, such as bone marrow and triggers high production of immature and abnormal shaped blood cells. Skilled medical officers are required to diagnose leukemia from blood smears. This poses a problem in remote areas and rural areas where there is a shortage of qualified medical personnel. This paper proposes a computer-aided diagnosis system that can detect and classify leukemia from blood microscopic images. Satisfactory preliminary experimental results demonstrate the efficacy of our system